Case report: CD7-targeted autologous CAR-T therapy for the treatment of T-cell acute lymphoblastic leukemia undergoing allogeneic peripheral blood stem cell transplantation in the long-term follow-up - Li, Lian-Lian; Xia, Yue-Ping; Li, Qianqian; Wang, Peng; Sun, Ping-Ping; Wang, Xing-Guang (Frontiers in Immunology, 2024)
IntroductionChimeric antigen receptor T-cell (CAR-T) therapy has emerged as a promising approach for treating relapsed/refractory (r/r) T-cell acute lymphoblastic leukemia (T-ALL). However, it is mostly used as a bridging therapy for allogeneic hematopoietic stem cell transplantation (allo-HSCT). Furthermore, secondary allo-HSCT is costly and associated with significantly high treatment-related mortality rate than the primary transplants. In this report, we present the case of an adult T-ALL patient who underwent CD7-targeted autologous CAR-T cell therapy that was not bridged with secondary allo-HSCT.Case presentationThe adult T-ALL patient relapsed for a third time after undergoing allogeneic peripheral blood stem cell transplantation (PBSCI) and achieving the first complete remission (CR1). Therefore, the patient was administered CD7-targeted autologous CAR-T cell therapy that was not bridged with secondary allo-HSCT. Towards this, the endogenous CD7-deleted CAR (CD7-CAR7) T cells were generated using CRISPR/Cas9 gene-editing technology. However, after the first infusion, the CD7 CAR-T cells did not show significant proliferation when analyzed at two weeks and the patient became positive for peripheral measurable residual disease (MRD). Therefore, after a two-week period, an augmented dose of CAR-T cells was administered. MRD was monitored in the peripheral blood and bone marrow samples. The patient achieved complete remission and did not require targeted treatment after the completion of CD7 CAR-T-cell therapy. The current follow-up data has shown that the patient is negative for MRD and has been disease-free for more than 42 months.ConclusionThe results of this case study provide evidence for the long-term efficacy of CD7-targeted autologous CAR-T-cell therapy without requiring secondary allo-HSCT in patients with r/r T-ALL that have relapsed after previous allogeneic PBSCT.